Increasing Self-Efficacy in Mentoring Relationships for Aspiring Entrepreneurs in Community Colleges. Issue 10 (3rd October 2022) - Villa, Lily Katerina; Ruth, Alissa; Luchmun, Rachel; Cantú, Elizabeth
ABSTRACT: Community colleges and universities increasingly offer entrepreneurial training to reach a larger portion of underrepresented students. This paper offers insights into what techniques mentors should employ to increase entrepreneurial self-efficacy among their mentees, particularly for diverse community college students. Using a five-week, social entrepreneurship training program at community colleges in the United States Southwest, this paper utilizes semi-structured interviews to understand the challenges and techniques that are associated with increasing mentees' entrepreneurial self-efficacy. Findings suggest that time and resources are the major constraints cited by both students and mentors. However, when mentors utilize storytelling, active listening, and open communication, they can further increase their mentees' entrepreneurial self-efficacy. These insights offer a valuable in-depth qualitative understanding of mentoring approaches that similar programs can integrate into their curricula.